Dataset for: Yield in all RTB crops in one cropping season along altitude gradients - Okonya, Joshua Sikhu; Carhuapoma, Pablo; Kroschel, Jürgen; Blomme, Guy; Legg, James P.; Njoroge, Anne (2022)
Yield in potato and sweetpotato in one cropping season along altitude gradients in Tanzania